No Matter What: A Qualitative Analysis of How LGBTQ Families and Allies Define Family through an Interactive Art Project. Issue 3 (3rd July 2019) - Willes, Karina; Jagiello, Kristy; Allen, Mike; Motel, Laura
ABSTRACT: The current study solicits individuals' artistic depictions and written definitions of family and provides comparisons to existing conceptualizations of family in communication research. Attendees of a Midwestern pride festival took part in an interactive art display, creating a visual representation of their own family on one side of a card and writing their definition of family on the other side. Both images and definitions focused on the ways family members' behaviors construct family. Participants' written responses describe family as unconditional, particularly in terms of love, support, and acceptance.